Different responses of heterogeneous graft presentations in bone reconstructions during sinus lift elevation surgery: an immunolabeling and histomorphometric study performed in rabbits - de Siqueira, Natália Barbosa [UNESP]; Ervolino da Silva, Ana Cláudia [UNESP]; Pereira, Rodrigo Dos Santos; Hochuli-Vieira, Eduardo [UNESP]; Lisboa-Filho, Paulo Noronha [UNESP]; Duailibe de Deus, Ciro Borges [UNESP]; Okamoto, Roberta [UNESP] (AME Publishing Company, 2022)
Background: This study aims to analyze the process of bone formation, maturation and mineralization promoted by Cerabone® functionalization with raloxifene in rabbit sinus floor elevation, through immunohistochemical and histomorphometric analyses. Methods: Twenty-four male rabbits had their maxillary sinuses filled. To access the sinus cavity a circular window with a diameter of 5 mm was made bilaterally to the midline of the nasal dorsum, the sinus membrane was detached and elevated using special curettes. Autogenous bone (G1), Cerabone® (G2), Cerabone® submitted to ultrasonic processing (G3), Cerabone® associated to raloxifene submitted to ultrasonic processing (G4) were used to fill the maxillary sinus, 14 and 42 days postoperatively. Immunohistochemical and histomorphometric analyses were performed at 14 and 42 days postoperatively. Results: At 14 days postoperatively: the immunolabeling for vascular endothelial growth factor (VEGF) was moderate in groups G1, G3 and G4, while in group G2, the same protein was expressed in a mild way. The immunolabeling for alkaline phosphatase (ALP) was moderate in all experimental groups. Histomorphometric analysis showed a greater amount of newly formed bone in groups G1 (55.2%) and G4 (50.1%), which differed statistically from groups G2 (37.5%) and G3 (38.2%). At 42 days postoperatively: receptor activator of nuclear factor kappa-B ligand (RANKL) immunolabeling was slight in G1, intense in G2 and moderate in G3 and G4. The tartrate resistant acid phosphatase (TRAP) protein was slightly expressed in all experimental groups. The osteocalcin (OCN) protein was moderately expressed in the G1 group and intensely in the G2, G3 and G4 groups. As for the histomorphometric analysis, the greatest amount of neoformed bone was found in group G1 (83.5%), followed by group G4 (75.0%). Less neoformed bone was observed in G3 (56.7%), followed by G2 (64.2%). Statistical differences were observed between all experimental groups. Conclusions: Better performance was observed in the group in which Cerabone was used in association with raloxifene (G4), with better bone formation responses compared to the experimental groups.
Keywords: Biocompatible materials; bone regeneration; bone substitutes; ultrasonic therapy